In-hospital management and outcomes of acute coronary syndromes in relation to prior history of heart failure. Issue 3 (June 2016) - Zhang, Hanfei; Goodman, Shaun G; Yan, Raymond T; Steg, Ph Gabriel; Kornder, Jan M; Gyenes, Gabor T; Grondin, Francois R; Brieger, David; DeYoung, J Paul; Gallo, Richard; Yan, Andrew T; ,
Introduction: The prognostic significance of prior heart failure in acute coronary syndromes has not been well studied. Accordingly, we evaluated the baseline characteristics, management patterns and clinical outcomes in patients with acute coronary syndromes who had prior heart failure. Methods and results: The study population consisted of acute coronary syndrome patients in the Global Registry of Acute Coronary Events, expanded Global Registry of Acute Coronary Events and Canadian Registry of Acute Coronary Events between 1999 and 2008. Of the 13, 937 eligible patients (mean age 66±13 years, 33% female and 28.3% with ST-elevation myocardial infarction), 1498 (10.7%) patients had a history of heart failure. Those with prior heart failure tended to be older, female and had lower systolic blood pressure, higher Killip class and creatinine on presentation. Prior heart failure was also associated with significantly worse left ventricular systolic function and lower rates of cardiac catheterization and coronary revascularization. The group with previous heart failure had significantly higher rates of acute decompensated heart failure, cardiogenic shock, myocardial (re)infarction and mortality in hospital. In multivariable analysis, prior heart failure remained an independent predictor of in-hospital mortality (odds ratio 1.48, 95% confidence interval 1.08–2.03, p =0.015). Conclusions: Prior heart failure was associated with high risk features on presentation and adverse outcomes including higher adjusted in-hospital mortality in acute coronary syndrome patients. However, acute coronary syndrome patients with prior heart failure were less likely to receive evidence-based therapies, suggesting potential opportunities to target more intensive treatment to improve their outcome.